A study on effectiveness of low temperature toward stored-product insects on stored rice / Ahmad Baihaqi Saidi - Saidi, Ahmad Baihaqi (Faculty of Plantation and Agrotechnology, 2018)
The storage of rice is part of the post-harvest system where the food passes from field to consumer. Insect associated with the storage and processing of grain could be major sources of spoilage and consequently economic loss. Instead of using insecticide to control the infestation that contains chemical substance which harmful to human health, a cold temperature was tested as physical control method. In order to replace the uses of insecticide that already resistance to stored-product beetles, the temperature was set up about -50C in cold room toward the three main stored grain insect such as Sitophilus oryzae, Tribolium castaneum and Oryzaephilus surinamensis. The experiment was conducted to verify the effectiveness of using cold temperature in order to control the infestation of insect on grain and the effect on eating quality of cooked rice. The result shows that the S. oryzae was more coldresistance insect compared to T. castaneum and O. surinamensis. For the reason, the percentage mortality of S. oryzae was lower at first day which is only 22.68% of insects were dead while T. castaneum and O. surinamensis which are 45.32% and 38.68% insects were dead respectively. At the end, the full mortality all three species of insects were reached at 72 hours (3rd day) of exposure. Within 72 hours of exposure, the insects were physically inactive in cold temperature during first 24 hours (1st day) and 48 hours (2nd days) before dead. The eating quality of cooked rice in terms of aroma, stickiness, taste, color and overall acceptability was not affected from the exposure of -5oC temperature within 72 hours (three days). In term of weight of grains also not affected at all after the treatment.